Role of a Teacher in Medical Education: A Faculty’s Perspective from HBS: Role of a Teacher in Medical Education: A Faculty’s Perspective - Awan, Amara Hayat; Ali, Sarah; Siddique, Uzma; Salman, Roma; Khan, Yasir; Ayub, Hassan (Pakistan Journal of Health Sciences, 2025)
Medical educators are vital in delivering knowledge and shaping students’ professional behaviour and critical thinking. However, their effectiveness is influenced by institutional support, teaching training, and the ability to adapt to innovative methodologies. Objectives: To assess faculty members’ perceptions, teaching practices, and institutional involvement in medical education and to explore the association between formal training and innovative teaching methods. Methods: A descriptive cross-sectional survey was conducted at HBS Dental College, Islamabad, including 85 faculty members. Data were collected using a structured questionnaire covering demographics, teaching methods, perceptions of educational roles, and barriers faced. Statistical analysis was performed using SPSS version 25.0, applying Chi-square, Mann-Whitney U, and Kruskal-Wallis tests. Results: Lecture-based teaching was universal, while small group teaching (68.2%) and PBL (41.2%) were also common. Only 35.3% of faculty had formal training in medical education. A significant association was found between training and the use of innovative methods (p=0.001). Reflective teaching scores were higher among trained faculty (p=0.049). Lack of time was the most reported barrier (69.4%). Conclusions: It was concluded that faculty with formal training were more likely to adopt innovative and reflective teaching practices. Addressing institutional barriers and investing in structured faculty development can significantly enhance the quality of medical education.